ABT-737, Synergistically Enhances Daunorubicin-Mediated Apoptosis in Acute Myeloid Leukemia Cell Lines - Hassan Dariushnejad; Nosratallah Zarghami; Mohammad Rahmati; Samaneh Ghasemali; Zohreh Sadeghi; Zahra Davoodi; Hossein Jafari Tekab; Masoud Gandomkar Ghalhar (Tabriz University of Medical Sciences, 2014)
Purpose: Intensive chemotherapy with daunorubicin (DNR) is associated with serious side effects in acute myeloid leukemia (AML) patients. In this study the effect of small-molecule BH3-mimetic, ABT-737, on the sensitivity of HL60 and U937 AML cell lines was investigated. Methods: The cytotoxic effects of DNR and ABT-737, alone or in combination were assessed using MTT assay and combination index analysis. The effects of treatments on the cell proliferation was determined by trypan blue assay. ELISA cell death assay was used for measurement of apoptosis. Results: IC50 values of DNR and ABT-737 were 2.52 and 0.59 μM for HL-60 cells line and 1.31 and 0.80 μM for U937 cell line at 24 h, respectively. Surprisingly, combination treatment significantly lowered the IC50 values in a synergic manner in both cell lines. Moreover, treatment with a mixture of two agents had more growth inhibition effect relative to the monotherapy. Results of apoptosis assay showed that the cytotoxic effects are related to the enhancement of apoptosis. Conclusion: Our study suggests that ABT-737 synergistically enhances the cytotoxic effect of DNR in AML cell lines and therefore may be useful to overcome chemoresistance of leukemia patients.